Pelatihan Bahasa Inggris bagi Mahasiswa Universitas Muhammadiyah Jambi - Syilvia Wenny J; Yahfenel Evi Fussalam; Yorina An’guna Bansa (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2024)
The importance of mastering English for students is something that needs to be considered, both by teaching staff and students themselves. This is because the ever-growing advances in science and technology require individuals to be able to master English language skills. This Community Service activity aims to provide training so that students can increase learning motivation, self-confidence, hone skills, increase knowledge and improve integrated abilities in English. Activities were carried out at the Muhammadiyah University of Jambi. This activity is aimed at students who are interested and want to improve their English language skills as many as 23 students. This English training received a positive response from students. It can also be concluded that this activity was successful and successful. This can be seen from changes in students' behavior and attitudes in dealing with English. Students begin to be confident and attractive in communicating using English.